Pengaruh Dosis Formula Amelioran dan Konsentrasi Pupuk Organik Cair terhadap Pertumbuhan dan Hasil Tanaman Pakcoy (Brassica rapa L.) Varietas Nauli F1 - Turmuktini, Tien; Roosma Ria, Elly; Luqman Agisni, Muhamad; Adviany , Ida; Kantikowati, Endang (Fakultas Pertanian Universitas Winaya Mukti, 2024)
This research aims to study the interaction between ameliorant formula dosage and concentration of liquid organic fertilizer on the growth and yield of Pakcoy nauli F1 varieties. The experiment was carried out in the farmer's garden in Gudang Village, Tanjungsari District, Sumedang Regency with a height of 870 meters above sea level (m asl), the time of the experiment was from July to November 2020. The research was conducted using an experimental method with environmental design using Randomized Group Design (RBD) factorial pattern consisting of two factors and repeated twice. The first factor is the dosage of the ameliorant formula with four levels: (0, 1, 2, 3 tons ha-1). The second factor was the concentration of liquid organic fertilizer at four levels: (0, 1, 2, 3 ml L-1 solution). The results showed that the interaction was not significant between the ameliorant formula dosage and the concentration of liquid organic fertilizer on the growth and yield of Pakcoy nauli F1 varieties. The results of the independent test of the ameliorant formula dosage affect growth and yield. The dosage of ameliorant formula 3 t ha-1 has a good effect on plant height at 7 DAS and 21 DAS and weight per plant, with a weight per hectare of 69.1 tonnes ha-1. The results of the independent test the concentration of liquid organic fertilizer (POC) have an effect on crop yield. The POC concentration of 3 ml L-1 solution gave the highest effect on the weight per plant, with a weight per hectare of 67.5 tonnes ha-1. The dosage of ameliorant formula and the concentration of liquid organic fertilizer increased the yield of plants by 21.32% and 18.86%, respectively, compared to the control. Keywords : Ameliorant formula, liquid organic fertilizer, pakcoy